2020
DOI: 10.1186/s40104-020-0434-6
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-mTOR pathway is involved in glucose-modulated amino acid sensing and utilization in the mammary glands of lactating goats

Abstract: Background: The local supply of energy-yielding nutrients such as glucose seems to affect the synthesis of milk components in the mammary gland (MG). Thus, our study was conducted to investigate the effects of locally available MG glucose supply (LMGS) on amino acid (AA) sensing and utilization in the MG of lactating dairy goats. Six dosages of glucose (0, 20, 40, 60, 80, and 100 g/d) were infused into the MG through the external pudendal artery to investigate the dose-dependent changes in mammary AA uptake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…This statement however, needs to be validated. Similar studies were reported in lactating goats (Cai et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…This statement however, needs to be validated. Similar studies were reported in lactating goats (Cai et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…After the knockout of STAT5 in the mouse mammary gland, the content of α-lactalbumin and β-lactoglobulin in milk was reduced by 23% and 39%, respectively [15]. In addition to STAT5, mammalian target of rapamycin (mTOR) also regulates the synthesis of milk proteins such as α-lactalbumin and α S1 -casein [44,45]. In bovine mammary epithelial cells, suppressor of cytokine signaling 3 inhibited STAT5a activity, and milk protein synthesis was significantly reduced after the phosphorylation of STAT5a was blocked [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Attention must be paid to mitophagy, which is a complex process and intersects with several other cellular events. Some mediators in mitophagy signaling pathways, such as mTOR and AMPK, also play roles in mitochondrial biogenesis ( 19 , 66 ), intrinsic fatty acid metabolism ( 141 ), glucose-modulated amino acid sensing and utilization ( 142 ), endothelium-dependent vasodilation in vessels ( 143 ), vascular smooth muscle cell proliferation and migration ( 144 ), suggesting that the manipulation of these may cause a series of unexpected side-effects.…”
Section: Future Perspectivesmentioning
confidence: 99%